Adverse pregnancy and perinatal outcomes in women with polycystic ovary syndrome undergoing assisted reproductive technology: a systematic review and meta-analysis - Xie, Nian; Zhao, Wenwen (Frontiers in Medicine, 2025)
BackgroundThe growing application of assisted reproductive technology (ART) has enabled more women with polycystic ovary syndrome (PCOS) to achieve pregnancy. However, the causal association between PCOS and reproductive outcomes remains uncertain. This study conducted a meta-analysis of cohort studies to explore the association between PCOS and adverse pregnancy and perinatal outcomes.MethodsA comprehensive search was carried out in PubMed, Web of Science, Embase, and the Cochrane Library to identify studies published prior to March 22, 2025. Cohort studies evaluating differences in adverse pregnancy and perinatal outcomes between women with PCOS and those without PCOS undergoing ART were included. Meta-analysis was conducted using R 4.3.2 and STATA 12.0 to estimate risk ratios (RRs) and 95% confidence intervals (CIs) for the association between PCOS and adverse outcomes. Study heterogeneity was assessed through Cochran’s Q test, I2 statistics, and 95% prediction intervals (PIs). Additionally, subgroup analysis, sensitivity analysis, and publication bias evaluation were performed to ensure the reliability and validity of the results.ResultsThis meta-analysis included 18 cohort studies, comprising 16,365 women with PCOS and 111,503 controls. Women with PCOS undergoing ART were found to have significantly higher clinical pregnancy rate (RR = 1.158, 95% CI: 1.004–1.335; 95% PI: 0.751–1.785) and live birth rate (RR = 1.084, 95% CI: 1.027–1.144; 95% PI: 0.827–1.361) compared to those without PCOS. However, these patients also exhibited an increased risk of miscarriage (RR = 1.301, 95% CI: 1.181–1.433; 95% PI: 0.917–1.957), gestational diabetes mellitus (GDM), hypertensive disorders of pregnancy (HDP), gestational hypertension, preterm premature rupture of membranes (PPROM), preterm birth (PTB) (RR = 1.259, 95% CI: 1.152–1.376; 95% PI: 1.143–1.387), and very preterm birth (VPTB), while showing a reduced risk of cesarean delivery (RR = 0.898, 95% CI: 0.810–0.994; 95% PI: 0.717–1.124). No significant differences were identified between PCOS and control groups regarding the risks of low birth weight, very low birth weight, macrosomia, small for gestational age, very small for gestational age, large for gestational age, or fetal malformation (all p > 0.05). Subgroup analysis of patients undergoing frozen embryo transfer (FET) yielded consistent results.ConclusionPCOS may affect pregnancy and perinatal outcomes in women undergoing ART, with an increased risk of miscarriage, GDM, HDP, gestational hypertension, PPROM, PTB, and VPTB. These results underscore the importance of tailored reproductive strategies and specialized perinatal management for women affected by PCOS.